Analisis Fabrikasi Desain Lamination Passive Mixing Microchannel Perangkat Mikrofluidik AcrylicMenggunakan Laser CO Daya Rendah - Badruzzaman, Badruzzaman; Baskoro, Ario Sunar; Siswantoro, A. Rizal (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2016)
Microfluidics device has been applied in the biomedical fields to manipulate fluids in a channel network with the dimensions between 5-500 µm. Microfluidics device is manufactured by microfabrication process consists of design, microstucturing and back-end process. One of microfluidics application is passive mixing microchannel. In this device, the fluids will flow through the channel without any moving part and pressure from outside to produce mixing fluid. It is important to design the form of channel to produce a good lamination passive mixing microchannel. In this study, the process of channel design was performed. Low power CO2 laser was used for microstucturing process as a cutting tool to produce microfluidic device on acrylic material. The parameters affect the output of the cutting process are the laser power, cutting speed and the design of channel. Surface roughness of designed channel was observed. Finally, back-end process was performed by joining process using thermal bonding method. From the experimental results, the design of lamination channel has an influence on all parameters to the surface roughnes.